MENINGKATAN KEAKTIFAN BERBICARA DAN KEMAMPUAN MATEMATIKA ANAK MELALUI MEDIA ULAR TANGGA - Titin Faridatun Nisa; Indri Wulan Suryani (Universitas Trunojoyo Madura, 2015)
Enhance The Activity of Speaking and Math Skills of Children Through The Medium of Snakes and Ladders. Language and cognitive development of children is necessary grown. So that learning becomes interesting and fun needed instructional media that holds the principle of learning while playing. Media snakes and ladders is a medium transport adapted from a game of snakes and ladders. This game can be used to foster language skills and mathematics children. This research aims to enhance the activity of speaking and improve math skills in children through a simple snakes and ladders media transport. This type of research is a action researh. This research was conducted in TK Pertiwi 1 Getas Tanjunganom Nganjuk District of as many as 25 children. The results showed an increase in the activity of speaking and math skills of children. Improving the ability of the child looks at prasiklus that the average child is capable of 11 children (44%) and an increase in the first cycle the average to 19 children (76%). In the second cycle there was an increase of 16% from the first cycle the average ability of children to 23 children (92%). Based on research conducted it can be concluded that learning by using snakes and ladders media transport can enhance the activity of speaking and simple math skills of children.